Client preferences and acceptability for medical abortion and MVA as early pregnancy termination method in Northwest Ethiopia - White Mary T; Sendekie Tegbar Y; Woldetsadik Mulatu A; Zegeye Desalegn T (BMC, 2011)
Abstract Background Increasing access to safe abortion services is the most effective way of preventing the burden of unsafe abortion, which is achieved by increasing safe choices for pregnancy termination. Medical abortion for termination of early abortion is said to safe, effective, and acceptable to women in several countries. In Ethiopia, however, medical methods have, until recently, never been used. For this reason it is important to assess women's preferences and the acceptability of medical abortion and manual vacuum aspiration (MVA) in the early first trimester pregnancy termination and factors affecting acceptability of medical and MVA abortion services. Methods A prospective study was conducted in two hospitals and two clinics from March 2009 to November 2009. The study population consisted of 414 subjects over the age of 18 with intrauterine pregnancies of up to 63 days' estimated gestation. Of these 251 subjects received mifepristone and misoprostol and 159 subjects received MVA. Questionnaires regarding expectations and experiences were administered before the abortion and at the 2-week follow-up visit. Results The study groups were similar with respect to age, marital status, educational status, religion and ethnicity. Their mean age was about 23, majority in both group completed secondary education and about half were married. Place of residence and duration of pregnancy were associated with method choice. Subjects undergoing medical abortions reported significantly greater satisfaction than those undergoing surgical abortions (91.2% vs 82.4%; P < .001). Of those women who had medical abortion, (83.3%) would choose the method again if needed, and (77.4%) of those who had MVA would also choose the method again. Ninety four percent of women who had medical abortion and 86.8% of those who had MVA would recommend the method to their friends. Conclusions Women receiving medical abortion were more satisfied with their method and more likely to choose the same method again than were subjects undergoing surgical abortion. We conclude that medical abortion can be used widely as an alternative method for early pregnancy termination.